(untitled) (Panauti Journal, 2023)
This paper aims to explore the household cost of basic education. The quantitative approach was used to walk around the household expenditure on basic education. Cluster sampling was used to select the sample units for the study. The 380 households were selected for the survey determined by Yamane’s formula of sample selection. The SPSS was used for the data analysis. The study found that households spend Rs. 31435 per year on basic education. Similarly, the per-child cost in public and private schools are Rs. 14285 and Rs. 49703, respectively. Moreover, parents pay Rs. 2090 annually to public schools, which is regarded as the government fully funds. So, it is concluded that free basic education is just a fable, not genuineness, in Nepal.